Performing Expertise: The Design of Audiovisual Links and the Construction of the Remote Expert Witness in Court. (October 2019) - Rowden, Emma; Wallace, Anne
This article reports on empirical research conducted into the use of audiovisual links (videolinks) to take expert testimony in jury trials. Studies reveal ambivalent attitudes to court use of videolink, with most previous research focussed on its use for vulnerable witnesses and defendants. Our study finds there are issues unique to expert witnesses appearing by videolink, such as compromised ability to gesture and interact with exhibits and demonstrative tools, and reductions in availability of feedback to gauge juror understanding. Overall, the use of videolinks adds an additional cognitive load to the task of giving expert evidence. While many of these issues might be addressed through environmental or technological improvements, we argue this research has broader ramifications for expert witnesses and the courts. The use of videolinks for taking expert evidence exposes the contingent nature of expertise and the cultural scaffolding inherent in its construction. In reflecting on the implications of these findings, and on the way that reliability, credibility and expertise are defined and established in court, we suggest a more critical engagement with the relationship between content and mode of delivery by stakeholders.